Effect of Seat Vibration on the Driver at High Speed Simulation Based on Unreal Engine 4 - Mohammad Ghiffari Abdullah; Yuniarto Agus Winoko (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2022)
Driving at high speed is one of the highest causes of accidents. The higher the speed of the vehicle, the narrower the driver's reaction time. In addition, not concentrating while driving is also the biggest contributor to accidents. For this reason, tools are needed to overcome these 2 things. Vibration is used in electronic devices. to give notifications to users such as cellphones and joysticks for that vibration can be used to alert the driver when the vehicle reaches high speed.Because the test carried out is related to high-speed vehicles, the test using simulation is carried out using an unreal engine 4, an unreal engine is used because it has many assets that can be directly used. This study aims to see the effect of vibration on concentration and concentration. driver reaction. The test was carried out by making scenario scenarios to test the participants' reactions and concentration. The scenario was divided into 3 types of light obstacles, heavy obstacles and sudden brakes, the test was carried out 2 times using a vibrating motor and when using a vibrating motor. This test is carried out to test the test taker's reflexes The purpose of this study was to analyze the effect of vibration on the vehicle seat on the concentration of the driver. Therefore, the test participants used were aged around 21-24 years to balance the participants. The results showed that participants who used a vibrating chair were more concentrated than those who did not use a vibrating chair.Ã‚Â